2011
DOI: 10.1002/ijc.27354
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus in vaginal intraepithelial neoplasia

Abstract: There are limited data on the prevalence and distribution of human papillomavirus (HPV) genotypes in vaginal intraepithelial neoplasia (VAIN). We sought to clarify this issue in a series of 450 VAIN cases with a confirmed diagnosis between 1990 and 2006. HPV genotyping was performed using paraffin-embedded specimens and polymerase chain reaction (PCR)-based methods. Multiple HPV types were validated by E6 type-specific PCR and direct sequencing. The HPV genotypes of the vaginal and cervical neoplasms were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
12
24
1
Order By: Relevance
“…In accordance with other studies we were able to demonstrate that the median age of women suffering from VAIN was 53 years [13, 14]. Furthermore, we were able to confirm that patients with LSIL (VAIN) were slightly younger compared to patients having HSIL (VAIN) [2].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with other studies we were able to demonstrate that the median age of women suffering from VAIN was 53 years [13, 14]. Furthermore, we were able to confirm that patients with LSIL (VAIN) were slightly younger compared to patients having HSIL (VAIN) [2].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, De Vuyst et al demonstrated an infection rate of LSIL (VAIN) in 107 VAIN cases and in 90,1% of 191 HSIL (VAIN) cases [7]. In contrast to these two studies, Chao et al reported a lower HPV detection rate of merely 69,3% (273 of 394 VAIN cases) in an monocentric study, using Ki-67 immunostaining [14]. …”
Section: Discussionmentioning
confidence: 99%
“…(36) They found that 69.3% of VaIN tissue blocks tested positive for HPV, and of those that tested positive, 17.9% had multiple HPV types present. The most common types present in the HPV-positive tissue blocks were HPV16 (35.5%), HPV58 (9.9%), HPV39 (8.4%), HPV33 (7.3%), and HPV53 (7.0%).…”
Section: Resultsmentioning
confidence: 99%
“…2,13,28 The prevalence of HPV in vaginal intraepithelial lesions parallels that of cervical intraepithelial lesions. [29][30][31][32] Our finding of a significantly increased incidence of VAIN1+ lesions in patients with positive hrHPV testing (55%) indicates that VAIN is associated with HPV infection. Of course, a selective bias may be present because hrHPV testing was not performed in all followup patients.…”
Section: Discussionmentioning
confidence: 99%